2014
DOI: 10.1098/rspb.2013.2473
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive value of same-sex pairing in Laysan albatross

Abstract: Same-sex pairing is widespread among animals but is difficult to explain in an evolutionary context because it does not result in reproduction, and thus same-sex behaviour often is viewed as maladaptive. Here, we compare survival, fecundity and transition probabilities of female Laysan albatross in different pair types, and we show how female-female pairing could be an adaptive alternative mating strategy, albeit one that resulted in lower fitness than male-female pairing. Females in same-sex pairs produced 80… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
7
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…One way in which it has been suggested to do so is by altering the fitness consequences of same-sex encounters (Lane et al, 2016). For example, same-sex female pairs of a female-biased population of Laysan albatross exhibit cooperative breeding (Young, Zaun, & VanderWerf, 2008), increasing their fitness and suggesting a role for SSB in facilitating the expression of alternative reproductive strategies (Young and VanderWerf, 2013). In males, SSB is generally expected to reduce the strength of aggressive interaction (Peschke, 1985;Preston-Mafham, 2006;Bailey and Zuk, 2009;Kuriwada, 2017), though evidence for this is mixed (Ruther and Steiner, 2008;Bailey and French, 2012;Lane et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…One way in which it has been suggested to do so is by altering the fitness consequences of same-sex encounters (Lane et al, 2016). For example, same-sex female pairs of a female-biased population of Laysan albatross exhibit cooperative breeding (Young, Zaun, & VanderWerf, 2008), increasing their fitness and suggesting a role for SSB in facilitating the expression of alternative reproductive strategies (Young and VanderWerf, 2013). In males, SSB is generally expected to reduce the strength of aggressive interaction (Peschke, 1985;Preston-Mafham, 2006;Bailey and Zuk, 2009;Kuriwada, 2017), though evidence for this is mixed (Ruther and Steiner, 2008;Bailey and French, 2012;Lane et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Research attempting to find and understand the ultimate causes of same-sex sexual behaviour has proposed several adaptive explanations 1 , 9 . The most common explanations include (i) social glue, which is a method to establish a strong social relationship, thereby reducing tension and conflicts 10 – 12 ; (ii) intersexual conflict, when the same-sex interaction establishes dominance in the hierarchy 13 or reduces the reproductive success of a competitor 14 ; (iii) practice, in which a young individual obtains mating experience 15 , 16 or gains the ability to improve their territory acquisition 17 ; or (iv) alloparenting, in which fluid sexuality of females may be a mechanism to possess allomothering investment from a female not related to the offspring 18 , 19 . On the other hand, non-adaptive explanations of same-sex sexual behaviour have been proposed, such as (i) mistaken identity, which explains this behaviour as an error due to lack of sex recognition 20 ; (ii) heterosexual deprivation when the population density is high and the sex ratio is skewed towards one sex 21 23 ; (iii) an evolutionary by-product, when selection acts on traits linked to sexual responsiveness 24 ; (iv) maladaptation if the individual is not well adapted to its environment 25 ; (v) intoxication, when methylmercury causes same-sex sexual behaviour and diminishes reproductive output as a result 26 ; or (vi) nutritional rewards, which is based on evidence that the brain network of the sexual response cycle pathway is similar to the pathway of the pleasure cycle during food acquisition, so that sex preference in later life depends on which sex was a caregiver during infancy 27 .…”
Section: Introductionmentioning
confidence: 99%
“…In another experimental study on the zebra finch ( Taeniopygia guttata ) 30 where one sex was eliminated, same-sex bonds occurred; the authors explained this behaviour by the social partnership hypothesis, a variation of the alloparenting hypothesis. Moreover, a study of a wild population of the Laysan albatross ( Phoebastria immutabilis ) revealed that f-f mating as a sexual strategy could be adaptive in a female-skewed population 16 . However, we were unable to find an experimental study on any one species that simultaneously tested the adaptive value of same-sex pairing under a skewed sex ratio towards both males and females.…”
Section: Introductionmentioning
confidence: 99%
“…Biases in the sex ratio favoring females, however, have been widely reported in seabirds leading to males breeding at an earlier age than females (Hunt et al ) and female–female social pairs (Ryder , Nisbet and Hatch , Lorensten et al , Nisbet et al , Bried et al ). Although female–female pairings often successfully fledge offspring that are sired via extra‐pair copulations, these pairings may not be as successful, on average, as male–female pairings (Young et al , Young and VanderWerf ).…”
mentioning
confidence: 99%
“…Biases in the sex ratio favoring females, however, have been widely reported in seabirds leading to males breeding at an earlier age than females (Hunt et al 1980) and female-female social pairs (Ryder 1983, Nisbet and Hatch 1999, Lorensten et al 2000, Nisbet et al 2007, Bried et al 2009). Although femalefemale pairings often successfully fledge offspring that are sired via extra-pair copulations, these pairings may not be as successful, on average, as male-female pairings (Young et al 2008, Young andVanderWerf 2013). Fisher (1958) proposed that equal investment in offspring of both sexes is an evolutionarily stable strategy and that frequency-dependent selection pressure should lead to the overproduction of the sex that was underrepresented in the adult population.…”
mentioning
confidence: 99%